Women are lack in religion and mind: The misunderstanding interpretation - Asar, Abdul Karim (Universiti Malaysia Pahang, 2019)
Women are lack in religion and mind; is an existing controversial issue among Muslim jurists, particularly among the modern scholars nowadays. Although this issue seems to be personal opinion to some people; but it actually a popular discourse debated by feminist movements all over the world. In fact, the gender equality is a standard norm promoted by the United Nations. The on-going debate among the Muslim jurists about the issue has affected Muslims, particularly to those who want to follow Islāmic way. It was originated from some controversial Islāmic texts; particularly the Prophetic tradition in Ṣaḥīḥ al-Bukhāri, no.: 298 which states that women are lack in religion and mind. Analytical study conducted by the researcher found that the lack mentioned in the Prophetic traditions actually is a figurative statement which has its specific implied meaning. This understanding is due to the contradicting practices of the Prophet Muḥammad himself to those gender-bias Islāmic legal texts.